Pengaruh Pemberian Arang Sekam dan Pupuk Kotoran Ayam terhadap Pertumbuhan dan Hasil Tanaman Sawi Hijau (Brassica juncea L.) - Allam Rinanda Yoedhistira; Ahmad Arif Darmawan (Fakultas Pertanian, Universitas Timor, 2022)
This study aims to (1) determine the effect of rice husk charcoal on the growth and yield of green mustard, (2) determine the effect of chicken manure fertilizer on growth and yield of green mustard, (3) determine the interaction of the treatment of rice husk charcoal and the dose of chicken manure fertilizer to growth and yield of mustard greens. This research was conducted in September 2019 until January 2020 at the Screen House of the Faculty of Agriculture, Jenderal Soedirman University. The experimental design used was a Complete Randomized Block Design (RCBD) with 2 factors. The first factor is the husk charcoal media, namely A0 = without the husk charcoal; A1 = Charcoal husk 12.5 tons / ha or equivalent to 50 g / polybag; A2 = husk 25 tons / ha or equivalent to 100 g / polybag; A3 = husk 37.5 tons / ha or equivalent to 150 g / polybag. The second factor is the dose of chicken manure fertilizer, P0 = without chicken manure fertilizer; P1 = chicken manure 5 ton / ha or equal to 20 g / polybag; P2 = chicken manure 10 tons / ha or equal to 40 g / polybag; P3 = chicken manure 15 tons / ha or equal to 60 g / polybag, each factor combined and obtained 16 treatment combinations. The treatment was repeated 3 times to get 48 experimental units. The observed variables were plant height (cm), number of leaves (strands), leaf area (cm), root length (cm), fresh plant weight (g), fresh crown weight (g), dry crown weight (g), weight fresh root (g), dry root weight (g). The data obtained were analyzed by analysis of variance. If the treatment is significantly different, it is further tested using DMRT at the 5% level. The results showed that the treatment of rice husk charcoal media 35.7 tons / ha or equivalent to 150 g / polybag gave the best dose of variable plant height, leaf area, fresh plant weight, weight of crown fresh 225.783 g, dry crown weight 33.444 g, fresh root weight 25.810 g. Application of chicken manure with a dose of 15 tons / ha or equivalent to 60 g / polybag produces a plant height of 42.325 cm, a leaf number of 10.833 strands, leaf area of 2,400,859 cm2, a fresh plant weight of 275,395 g, a fresh crown weight of 245,428 g, dry crown weight of 44,021 g, fresh root weight of 26,968 g, and dry root weight of 0.034 g, and there was no interaction between the husk charcoal media and chicken manure fertilizer to increase the growth and yield of mustard plants.